CEO early-life disaster experience and stock price crash risk - Chen, Yangyang; Fan, Qingliang; Yang, Xin; Zolotoy, Leon (Journal of corporate finance (Amsterdam, Netherlands), 2021)
We study the impact of CEO early-life disaster experience on stock price crash risk. Using a longitudinal sample of U.S. firms, we document that firms led by CEOs with early-life disaster experience have higher stock price crash risk. Our findings are consistent with CEOs who experienced early-life disasters being more risk tolerant, and thus more willing to accept the risks associated with bad news hoarding, engendering formation of stock price crashes. In cross-sectional analyses, we find that the effect of CEO disaster experience is amplified when a CEO has greater equity compensation-based incentives and power over corporate board to hoard bad news. Reinforcing bad news hoarding narrative, we also find that stocks of the firms led by CEOs with early-life disaster experience exhibit stronger asymmetric response to bad versus good news disclosures and are more likely to experience crashes accompanied by breaks in the strings of uninterrupted earnings increases. Further, consistent with early-life disaster experience making CEOs more risk tolerant, we find that firms led by CEOs with early-life disaster experience tend to have higher cash-flow volatility and stock return volatility. Evidence from supplemental analysis suggests that the impact of CEO early-life disaster experience on crash risk varies in a curvilinear manner with the severity of disaster. •Firms led by CEOs with early-life disaster experiences have higher stock price crash risk.•The effect is amplified when a CEO has greater equity-based incentives to hoard bad news.•The effect is amplified when a CEO has greater power over corporate board to hoard bad news.•The effect varies in a curvilinear manner with the severity of disaster.